PENGARUH INVESTMENT OPPORTUNITY SET, KEBIJAKAN UTANG, PERTUMBUHAN PERUSAHAAN DAN COLLATERALIZABLE ASSETS TERHADAP KEBIJAKAN DIVIDEN - Made Sukarti; Rapel Rapel; Rosel Rosel (Universitas Palangka Raya, 2022)
This study aims to examine the effect of investment opportunity set, debt policy, company growth and collateralizable assets on dividend policy. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (BEI) 2016-2019.The sampling technique used in this study was purposive sampling with a sample size of 30 manufacturing companies listed on the Indonesia Stock Exchange (BEI) 2016-2019. The data analysis used in this research is multiple linear regression analysis. The results of this study indicate that the investment opportunity set has a positive effect on dividend policy, while debt policy, company growth and collateralizable assets have a negative effect on dividend policy. While the simultaneous test results show that the investment opportunity set, debt policy, company growth and collateralisable assets together have a positive effect on dividend policy